Breast Cancer: Making Sense of the Numbers - Martha C. Monroe; Barbara F. Shea; Linda B. Bobroff (EDIS, 2014)
A breast cancer diagnosis is always a challenge to the patient and her family.* People react in different ways to a breast cancer diagnosis. Some breast cancer patients want to take an active role in understanding and choosing their treatment, and others prefer to leave decisions to their health care providers. This revised 5-page fact sheet, first in a 12-part series on breast cancer, provides information that will help persons who want to understand and be actively involved in treatment decisions. Written by Martha C. Monroe, Barbara F. Shea, and Linda Bobroff, and published by the UF Department of Family, Youth and Community Sciences, December 2014. (Photo: iStock/Thinkstock)